Some applications of the Jung-Kim-Srivastava Integral Operator - Liu,Jin-Lin
In this paper we derive some interesting properties of certain integral operator I(superscript σ) which was considered recently by Jung, Kim, and Srivastava.
Keywords: Analytic; Subordination; Integral operator